Perilaku agresi masyarakat pada saat pendisiplinan protokol kesehatan oleh petugas: Benarkah ada pernanan self-awareness? - M. Ali Shodiqin; Anrilia Ema Mustikawati Ningdyah (INNER: Journal of Psychological Research, 2022)
Aggressive behavior in the community when disciplining health protocols needs to be given a focus of attention because there are many negative impacts that arise both in terms of morality and discipline towards regulations. This study was intended to examine the relationship between self-awareness and aggressive behavior. Participants in this study were 80 people with the criteria of domicile in Surabaya and the age range of 18-40 years. The data collection technique used purposive sampling. The data in this study used the self-awareness scale (α= 0.930) and Aggression Behavior (α = 0.895) with the preparation by the researcher himself. Analysis of the data used is the Spearman rho Correlation technique, the correlation coefficient value rxy=0.357 with a significance of p=0.001 (p <0.05). It can be concluded that both variables partially have a significant negative effect. The results of the study can be used as the basis for controlling the aggressive behavior of the community by related parties. Keywords: self-awareness; aggressive behavior